The design of solar power thermoelectric radiant panel as cooling system in small buildings under tropical climate - 'Amir, Muhammad; Mohd Redzuan, Farah Liana Binti; Jamani Jamian, Jasrul; Ahmad Zaki, Sheikh; Faiz Mohammad, Ahmad; Yakub, Fitri; Mohd Maruai, Nurshafinaz; Sukri, Mohamed (Creative Science, 2023)
The usage of an air–conditioning (AC) system in any building is necessary to maintain its indoor thermal comfort and health. However, this system consumes a lot of energy, while the usage of refrigerant causes irreversible damage to the ozone layer. To solve this problem, a solar thermoelectric radiant panel (PV-TERP) system has a high potential in replacing conventional AC system because it requires no refrigerant and easier to be controlled due to the absence of moving and mechanical parts such as water pumps, compressors, including auxiliary and hydronic pipes. Meanwhile, the usage of solar energy in the PV-TERP system can also help reduce fossil energy consumption and carbon emissions. The main objective of this work is to design a new PV-TERP system for replacing conventional AC systems in buildings located in tropical climate countries, like Malaysia. It is found that the designed PV-TERP system can provide up to 4.84 kW of cooling power, which is about 0.6% higher than the cooling load of targeted rooms. Here, the targeted rooms operate under indoor parameters within the acceptable range of ASHRAE standard-55. The obtained results clearly show that the new design is applicable to be used as a cooling system for the targeted building. In the future, it is then essential to understand the thermal properties and mechanism of the design via simulation process, followed by experimental validation to support the design feasibility. In conclusion, this new design of PV-TERP will lead the path toward expanding renewable energy applications for cooling purposes in sustaining and preserving the environment. HIGHLIGHTS Alternative cooling system in replacing air-conditioning (AC) system for maintaining indoor thermal comfort without harming the environment. Designation of the PV-TERP system as a cooling system for building in a tropical country (Malaysia) under indoor parameters within the acceptable range of ASHRAE Standard-55. The designed PV-TERP is refrigerant-free and operates using renewable energy, which can sustain and preserve the environment for a better future. GRAPHICAL ABSTRACT